Pelatihan Pembuatan Keripik dari Limbah Kulit Ikan Tuna kepada Kelompok Perempuan Binaan Lembaga Natural Aceh - Lia Handayani; Nurhayati Nurhayati; Cut Rahmawati; Azwar Thaib; Faisal Syahputra; Ainal Mardhiah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
PT. Sure Pacific Tuna and PT. Aceh Lampulo Jaya Bahari are 2 frozen tuna fish processing companies that produce fish skin waste, and have not been utilized economically. The majority of people work as fishermen and some groups of women work to process oysters into crackers. Utilization of tuna skin waste will provide many good impacts for the community because besides that it can also increase income for the company, besides that it can add entrepreneurial insight for participants and provide additional income for families. The targets of this activity are housewives, fishermen who generally also work as oyster seekers who also process oysters into crackers so that they have no difficulty understanding the process of making crackers. The results of this activity are very satisfactory because the participants of the activity can understand the process of processing tuna skin to be chips and able to process chips independently.